Beija-flores e seus recursos florais em uma área de campo rupestre: composição de espécies, sazonalidade e rede de interações - Licleia da Cruz Rodrigues (2011)
Hummingbirds are generalist birds that use of the nectar. They exploit a variety of flowers adapted to pollination by other groups of pollinators in their diet. Because hummingbirds are highly dependent on nectar and have high energy requirements, the availability of flowers may cause these birds to move within and between habitats in search of these resources. Although a number of recent studies of mutualism between plants and animals give emphasis on network interactions, few studies on plant-hummingbird communities have focused this aspect. Over two years a study on the community of hummingbirds and their flowers was conducted at Alto do Palácio region (AP) in the Parque Nacional da Serra do Cipó. I analyzed species composition, seasonality, the interaction network and population parameters of Augastes scutatus, the most abundant species of hummingbird in the study area. Monthly visits to the area were conducted to record plants and heir hummingbirds by focal observations, and mist netting. The monthly density of flowers was recorded in three vegetation types of the AP. The community of hummingbirds was composed of 13 species but only six species visited flowers of 51 plant species, of which 56.9% were non-ornitophilous species. Only one plant species was always visited illegitimately by hummingbirds. During the studied period there was a succession offlowering, occurring overlap between plant species, enabling the maintenance of resident hummingbird species in AP. The composition of hummingbird species varied with vegetation type, due to habitat preference of the species that make up this community, and the energy availability of floral resources, which demonstrates the ability of hummingbirds to locate different floral resources. The network of interactions between plants and hummingbirds proved to be asymmetrical in distribution and degree of dependency among both hummingbirds and plants species. However, this network showed a low degree of nestedeness due to specialization of some hummingbird species on the type of flowers visited and the short period of occurrence of some of these birds. The centrality and strength of the species that comprise the network of interactions were related to the abundance and time of occurrence of hummingbird species, but not of plant species. Augastes scutatus exhibited high importance in this network of interactions, being considered as key species since it was the main visitor of the plants, which is related to its high abundance and residence in the study area.